SIMILARITIES AND DIFFERENCES OF TENSES IN ENGLISH AND UZBEK LANGUAGES. - Shahriddinova Gavhar; Muhammadiyev Aziz Shavkatovich (TADQIQOTLAR.UZ, 2024)
Annotation: This article examines tenses in English and Uzbek by providing specific examples of differences and similarities between the two languages. We will study how to employ grammatical aspects of tenses in both languages in this article